Novel drug delivery carrier: resealed erythrocytes - SHASHANK SHAH (International Journal of Pharma and Bio Sciences, 2011)
Nowadays, there are 30 and more main drug delivery products in the market. The total annual income for all of these is approximately US43 billion with an annual growth of 15 % (based on global product revenue). The reasons for this increasing interest in drug delivery are due to the increasing need of safe drugs, capable of reaching the target and with minimal side effects. In fact the main problems associated with systemic drug administration are essentially related to the bio-distribution of pharmaceuticals throughout the body. Resealed Erythrocytes are biocompatible, biodegradable, possess long circulation half-life and can be loaded with variety of active substances. Carrier erythrocytes are prepared by collecting blood sample from the organism of interest and separating erythrocytes from plasma. By using various methods the cells are broken and the drug is entrapped into the erythrocytes, finally they are resealed and the resultant carriers are then called "resealed erythrocytes". So many drugs like aspirin, steroid, cancer drug which having many side effects are reduce by resealed erythrocyte.